Analysis of Fuel Level Monitoring System Design In Fuel Tank Generator Set - Widianto, Maulana Luky; Nurhadi (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
The fuel monitoring system for Generator Sets in mining areas is currently non-existent, resulting in an inability to determine fuel depletion status, consequently rendering the units inoperable and not functioning as intended. This research aims to design a fuel monitoring system for generator set fuel tanks using LoRa communication and ultrasonic sensors. Additionally, it seeks to investigate the effects of different LoRa bandwidth variations and distances on the time of air (ToA) for fuel level data transmission. The study employs an experimental method to explore the relationship between LoRa bandwidth variations (KHz) of 125, 250, and 500 KHz, as well as distances between modules (m) of 25, 50, 75, and 100 meters, concerning the time of air (ToA) for fuel level data transmission. The results of this research include the design and implementation of a fuel level monitoring device. The study demonstrates that the shortest data transmission time occurs at a bandwidth of 125 KHz and a distance of 25 meters, while the longest data transmission time occurs at a bandwidth of 500 KHz and a distance of 100 meters. This indicates that both bandwidth and distance significantly influence the time of air (ToA) or data transmission duration for fuel level monitoring.